The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acscatal.8b04039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pH on Aqueous-Phase Phenol Hydrogenation Catalyzed by Carbon-Supported Pt and Rh

Abstract: In aqueous phase, the rates of hydrogenation of aromatic substrates such as phenol on Pt/C and Rh/C are influenced by varying activity of hydronium ions. Decreasing the pH from 8 to 1 increases the rate of hydrogenation of phenol on Pt at 20 bar H 2 and 80 °C by 15-fold. This increase is attributed to weakening of the hydrogen binding energy (HBE) on the metal surface with decreasing pH. A weaker HBE at lower pH is also predicted by ab initio molecular dynamics simulations, providing atomistic insight into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 66 publications
4
39
0
Order By: Relevance
“…Two catalysts, Pd/HNO 3 CF‐12h and Pd/HNO 3 CF‐6h, were investigated at pH 2.5, 5.2, and 10.5 (Figure S17). The ECH rates increased with decreasing pH, paralleling a recent study . Importantly, the differences between both catalysts become more pronounced as the pH increases.…”
Section: Figuresupporting
confidence: 85%
“…Two catalysts, Pd/HNO 3 CF‐12h and Pd/HNO 3 CF‐6h, were investigated at pH 2.5, 5.2, and 10.5 (Figure S17). The ECH rates increased with decreasing pH, paralleling a recent study . Importantly, the differences between both catalysts become more pronounced as the pH increases.…”
Section: Figuresupporting
confidence: 85%
“…They found that the higher reaction rate is attributed to weakening of the hydrogen binding energy on the metal surface with decreasing pH. [34] Comparing the catalytic results with the ones reported in literature (Table 1), commercial Pd/AC 5 % in our operating conditions shows good catalytic performance during both Na-Muc and t,t-MA hydrogenation. Low pressure and temperature allowed to reach full conversion and high AdA yield avoiding the use of pressurized hydrogen, which is a matter of concern for industrial safety reasons.…”
Section: Hydrogenation Of Transtrans Muconic Acidsupporting
confidence: 73%
“…reported the same catalytic behavior during phenol hydrogenation. They found that the higher reaction rate is attributed to weakening of the hydrogen binding energy on the metal surface with decreasing pH …”
Section: Resultsmentioning
confidence: 99%
“…For example, during the hydrogenation of maleic acid at a wired Pt–water interface, changes in rate with H 2 pressure were attributed to spontaneous electrical polarization, without accounting for changes in chemical driving force (i.e., the H 2 reaction order). 46 Likewise, pH-dependent CO oxidation 47 , 48 and phenol hydrogenation 49 rates were indirectly attributed to spontaneous polarization on the basis of shifts in the CO infrared spectrum and molecular dynamics simulations, respectively, but could not rule out contributions from chemical pH effects. Thus, it remains unclear whether spontaneous electrical polarization indeed plays a role in liquid-phase thermochemical heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%